Geographic and socio-economic variation in markers of indoor air pollution in Nepal: evidence from nationally-representative data - Saruna Ghimire; Shiva Raj Mishra; Abhishek Sharma; Adugna Siweya; Nipun Shrestha; Bipin Adhikari (BMC, 2019)
Abstract Background In low-income countries such as Nepal, indoor air pollution (IAP), generated by the indoor burning of biomass fuels, is the top-fourth risk factor driving overall morbidity and mortality. We present the first assessment of geographic and socio-economic determinants of the markers of IAP (specifically fuel types, cooking practices, and indoor smoking) in a nationally-representative sample of Nepalese households. Methods Household level data on 11,040 households, obtained from the 2016 Nepal Demographic and Health Survey, were analyzed. Binary logistic regression analyses were conducted to assess the use of fuel types, indoor cooking practices, indoor smoking and IAP with respect to socio-economic indicators and geographic location of the household. Results More than 80% of the households had at least one marker of IAP: 66% of the household used unclean fuel, 45% did not have a separate kitchen to cook in, and 43% had indoor smoking. In adjusted binary logistic regression, female and educational attainment of household's head favored cleaner indoor environment, i.e., using clean fuel, cooking in a separate kitchen, not smoking indoors, and subsequently no indoor pollution. In contrast, households belonging to lower wealth quintile and rural areas did not favor a cleaner indoor environment. Households in Province 2, compared to Province 1, were particularly prone to indoor pollution due to unclean fuel use, no separate kitchen to cook in, and smoking indoors. Most of the districts had a high burden of IAP and its markers. Conclusions Fuel choice and clean indoor practices are dependent on household socio-economic status. The geographical disparity in the distribution of markers of IAP calls for public health interventions targeting households that are poor and located in rural areas.